2012
DOI: 10.1021/ac3018108
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Response of IMS Detector for Mixtures Containing Two Active Components

Abstract: This study describes the relationship between the output signal of the ion mobility spectrometry (IMS) detector and the concentrations of two compounds being simultaneously introduced into the reaction section. Investigations were performed for three pairs of compounds, that is, dimethyl methylphosphonate (DMMP) and acetone, methyl tert-butyl ether (MTBE), and acetone, as well as trimethylamine (TMA) and n-nonylamine (NA). Vapors of the investigated compounds were produced in a two-channel generator with perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…If the depletion of the reactant ions is the limiting factor for the response, it is most likely that the acetone peak is still not separated well enough from the reactant ion peak, leading to a smaller difference current even though most reactant ions are already depleted. In this case, the increasing sensitivity at high concentrations could be attributed to the formation of a so-called dimer ion [32] containing two acetone molecules. As such an ion is significantly slower, it would be separated better, leading to an increase in sensitivity.…”
Section: Experimental Results From the Current Demonstratormentioning
confidence: 97%
“…If the depletion of the reactant ions is the limiting factor for the response, it is most likely that the acetone peak is still not separated well enough from the reactant ion peak, leading to a smaller difference current even though most reactant ions are already depleted. In this case, the increasing sensitivity at high concentrations could be attributed to the formation of a so-called dimer ion [32] containing two acetone molecules. As such an ion is significantly slower, it would be separated better, leading to an increase in sensitivity.…”
Section: Experimental Results From the Current Demonstratormentioning
confidence: 97%
“…We believe that the change could be due to sample solvent somehow "overloading" the drift tube on this one day, since the next day's measurement of the mobility of the first peak was as expected. It has been reported that mobility of monomers can be more dependent on measuring conditions than dimers [57]. Interestingly, when hexane:toluene (9:1) is used, a new peak with a lower mobility, K 0 ϭ 1.63 cm 2 /Vs, appears while measuring mass-selected mobility of the ion m/z 80 (Figure 3b).…”
Section: Pyridinementioning
confidence: 92%
“…Analysis of the quantitative aspects of the application of dopants was presented in [86]. The use of acetone as a dopant can reduce the analytical signal when the analyte and the dopant PA are similar.…”
Section: Quantitative Aspects Of Using Dopantsmentioning
confidence: 99%
“…Therefore, in many analytical applications, it is necessary to ensure the stability of the concentration of the admixture. Permeation standards constructed from vials covered by membranes are often used as sources of dopants [79,86].…”
Section: Introductionmentioning
confidence: 99%